2016
DOI: 10.3109/08820538.2016.1157612
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume is Associated with Diabetic Macular Edema in Patients with Type-2 Diabetes Mellitus

Abstract: High MPV values may be an important risk factor for the development of PDR and DME in patients with diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
4
16
0
Order By: Relevance
“…In our study diabetic ZDF rats had increased MPV values in comparison with the healthy lean control [54]. In diabetic patients there is usually higher value of PDWc-the hematological parameter that presents an indicator of variation in platelets' size and activity [79,82]. In our previous research [83], we observed that the rise in the secondary symptoms of T2DM complications caused by high-energy diet was accompanied with disturbed hematological parameters.…”
Section: Hematological Parameters Of Zdf Ratssupporting
confidence: 51%
See 2 more Smart Citations
“…In our study diabetic ZDF rats had increased MPV values in comparison with the healthy lean control [54]. In diabetic patients there is usually higher value of PDWc-the hematological parameter that presents an indicator of variation in platelets' size and activity [79,82]. In our previous research [83], we observed that the rise in the secondary symptoms of T2DM complications caused by high-energy diet was accompanied with disturbed hematological parameters.…”
Section: Hematological Parameters Of Zdf Ratssupporting
confidence: 51%
“…Usually diabetic patients have increased MPV values [79] correlated with a large thrombocyte size that are more reactive and aggregable [77] which can upset hemostatic system during the diabetic state [80]. In diabetes the risk of retinopathy onset increases with higher MPV [79,81]. In our study diabetic ZDF rats had increased MPV values in comparison with the healthy lean control [54].…”
Section: Hematological Parameters Of Zdf Ratssupporting
confidence: 45%
See 1 more Smart Citation
“…Of the 68 studies, 9 articles were excluded since control group’s subjects were not DM patients, but healthy people, and 11 articles were removed owing to the lack of available data. Finally, 48 articles with 9118 patients were enrolled in this meta-analysis [ 21–23 , 29–73 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in retrospect, the conclusions regarding the relationship of NLR, MPV, and PDW to the development and progression of DR and DN were conflicting [ 21–23 ]. One of the reasons for the inconsistency might be that the sample size was small in a single study and the power of statistical results was challenged.…”
Section: Introductionmentioning
confidence: 99%